The shadow of Selma - Street, Joe; Knight, Henry, 1982- (University Press of Florida, 2018)
The Shadow of Selma is the first thorough analysis of the historical importance and legacy of the 1965 campaign for civil rights in Selma, Alabama, and the consequent Voting Rights Act, which is among the most important pieces of legislation in American history. It considers the historical memory of the Selma campaign, particularly examining the competing narratives of Selma in popular media and cinema.